Intellectual Development of Maqashid Al-Syariah: A Thought of Jaseer Auda - Alamudi, Ichwan Ahnaz (Sharia Faculty Islamic Economic Law Study Department, 2024)
Maqashid Sharia is an important thing to study in legal sharia. Because, maqashid is the main basis in understanding the source of the law revealed by God to His messenger Prophet Muhammad SAW. in the form of the Qur'an and Hadith. Maqashid develops by making it a key in solving contemporary cases and challenges. Therefore, maqashid is pretexted as a bridge in carrying out ijtihad against the renewal of Islamic law. The theory put forward by Jasser Auda discusses three main sciences at once about maqashid sharia, ushul fiqh and the system approach, after being separated and not becoming a unit, it is successfully connected into an integrated unity.